Psychometric analysis of the Self-Report Questionnaire (SRQ) as an indicator of depression and anxiety in users of health establishments in Lima - Robles-Arana, Yolanda (2023)
Mental disorders have a high prevalence among people who seek care in health facilities for physical ailments without being properly identified and treated. The Self Report Questionnaire (SRQ) has been designed to detect possible cases and is widely used in the primary care field. Objective: To establish the predictive power of items of the SRQ-27 in the identification of depressive and anxiety disorders in users of health establishments in Lima. Method: The study utilized data of the sample of 10 885 people from the Epidemiological Study of Mental Health in health establishments of Metropolitan Lima 2015. The responses to the SRQ-27 and its relationship with the presence of anxiety and depression, established by the Mini Neuropsychiatric Interview, were analyzed using descriptive statistics, association tests, and AUC-ROC analysis of each item. Results: Two items referring to “feeling sad” and “crying” had the highest predictive power for the presence of depression (AUC ROC 0.766 and 0.719), whereas the item referring to “feeling nervous or tense” had the highest power for anxiety (AUC ROC 0.695). Nine other, common to both disorders, also showed to be effective (AUC ROC >0.60) in their identification. Conclusions:Three SRQ-27 items were identified as having the highest predictive power for the detection of depression and anxiety in general, while items with the highest predictive power are common for both conditions.